Transformational leadership and the medication-error management climate - Alharbi, Fahad Abdullah; Alshammari, Abdulaziz Hamdi; Altalhi, Osamah Hassen; Aldughayyim, Fahad Saleh; Alotaibi, Waad Mohammed (International journal of health sciences, 2024)
Background: Transformational leadership is a prominent leadership style renowned for its potential to yield positive outcomes in various sectors, including healthcare, education, and academia. It has been associated with fostering staff well-being, motivation, professionalism, and retention, while simultaneously shaping organizational culture and employee behavior. Aim: The aim of this study is to examine the relationship between transformational leadership styles and the medication-error management environment in Saudi hospitals. Method: A systematic review and analysis of five studies were conducted, all of which received a "Good" quality rating. These studies collectively investigated the relationship between transformational leadership and a range of important outcomes. Wu et al. (2020) highlighted the positive impact of transformational leadership on enhancing healthcare staff well-being. Novita et al. (2022) revealed the mediating role of work motivation in the connection between transformational leadership and teacher professionalism. Abu-Rumman (2021) underscored the significant influence of transformational leadership on human capital development in academia. Reinhardt et al. (2022) demonstrated the efficacy of transformational leadership in retaining nursing staff. Kao et al. (2023) unveiled the intricate connections between leadership, organizational climate, and employee behavior.